Analisis Pelaksanaan Pendaftaran Tanah Sistimatis Lengkap (PTSL) Kantor Pertanahan Kabupaten Halmahera Timur (Studi Pelaksanaan Program Tingkat Desa Di Kabupaten Halmahera Timur) - Anwar Ahmad; Abdul Wahid Kamma; Abdul Kadir Ali (Jurnal Ilmiah Wahana Pendidikan, 2023)
Complete Systematic Land Registration is the process of land registration for the first time which is carried out simultaneously for all land registration objects throughout Indonesia in one village or sub-district area, including the collection and determination of the correctness of physical and juridical data regarding one or several land registration objects for the purpose of registration. .The purpose of this study is to understand how the Implementation of Issuing Land Certificates through the Complete Systematic Land Registration Program (PTSL) is carried out in East Halmahera Regency, especially in the case study conducted in Maba Sangaji Village, Maba City District. This research will be carried out systematically and in detail, and will analyze the factors that impede the implementation of the program, especially at the East Halmahera District Land Office which is implementing the program in Maba Sangaji Village. This study uses descriptive qualitative research methods with a focus on observing people's behavior through words or utterances. The selection of qualitative methods aims to provide a more detailed description, explanation and understanding of the problems studied by studying individuals, groups or events as a whole.